2012
DOI: 10.4269/ajtmh.2012.11-0424
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rickettsioses and Q fever in Sri Lanka

Abstract: Abstract. Current serological evidence suggests the presence of scrub typhus and spotted fever group (SFG) rickettsiosis in Sri Lanka. Our objective was to identify rickettsial agents/Q fever as aetiological causes for patients who were presumed having rickettsioses by the presence of an eschar or a rash. Sera from patients with unknown origin fever from Matara were tested by immunofluorescence for SFG rickettsial antigens, typhus group rickettsiae, Orientia tsutsugamushi, and Coxiella burnetii antigens. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Microimmunofluorescence (IFA) is the reference technique for diagnosing Q fever. 16,17 However this was not performed because IFA requires highly experienced technicians, 9 and such expertise was not available in the local laboratories that participated in this study. As a result, in the absence of serological data, we could not determine if our C. burnetii-positive patients were suffering from acute Q fever or Q fever endocarditis.…”
Section: Discussionmentioning
confidence: 97%
“…Microimmunofluorescence (IFA) is the reference technique for diagnosing Q fever. 16,17 However this was not performed because IFA requires highly experienced technicians, 9 and such expertise was not available in the local laboratories that participated in this study. As a result, in the absence of serological data, we could not determine if our C. burnetii-positive patients were suffering from acute Q fever or Q fever endocarditis.…”
Section: Discussionmentioning
confidence: 97%
“…Although R. sibirica mongolitimonae was firstly isolated from Hyalomma asiaticum collected in China [7], to date, human cases of R. sibirica mongolitimonae infection have been never described in Asia. Current serological evidence suggests the presence of scrub typhus and SFG rickettsiosis including Rickettsia conorii [8] in Sri Lanka [9] (Table 1). However, serology makes difficult to identify the infecting rickettsial species because of cross-reactivity among antigens of pathogens within the same genus.…”
Section: Introductionmentioning
confidence: 99%
“…A hospital based study conducted in District General Hospital, Matara in 2009 identified 25 (14%) patients with scrub typhus, 6 (3%) with SFG rickettsioses, 3 (1.6%) with acute Q fever, 3 (1.6%) with murine typhus and 3 (1.6%) infected by Rickettsia felis. 21 A study conducted at Teaching Hospital, Karapitiya where 883 paired sera were analyzed, identified 17.7% with confirmed rickettsioses. Spotted fever was the most common type of rickettsioses identified in this study.…”
Section: Geographical Distribution Of Rickettsioses In Sri Lankamentioning
confidence: 99%
“…33 In studies conducted in Sri Lanka, inoculation eschar has been mostly associated with scrub typhus. 21 The proportion of patients with confirmed scrub typhus with eschar ranged from 25% to 89%. 16,21,23 Rash is generally associated with a lesser proportion of patients with scrub typhus, sometimes being absent.…”
Section: Clinical Presentation Of Rickettsiosesmentioning
confidence: 99%
See 1 more Smart Citation